Baggley C. R., Read M. G. Investigation of a thermo-fluidic exchange pump in trilateral flash and organic Rankine cycles / trans. from Engl. M. A. Fedorova - M. A. Fedorova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
It is well known that large amounts of energy loss occurs at low temperature states in a wide range of industrial processes., The recovery and reuse of this energy is at the forefront of increasing the overall efficiencies of industrial systems. The aim of this paper is to investigate the effectiveness of using a Thermo-Fluidic Exchange (TFE) pump at low temperature conditions in both a Saturated-Vapour Organic Rankine Cycle (SORC) and a Trilateral Flash Cycle (TFC). For some low temperature applications, TFCs have been shown to achieve higher net power output than conventional SORCs, due to their ability to extract more heat from the source fluid. This is the subject of current research as a result of advancements made in the design of positive displacement machines for operation as twophase expanders. Conventional turbines cannot be used for TFCs as they must operate in the vapour phase. One drawback of the TFC is the higher working fluid mass flow rate required. Depending on the scale of the system, this can potentially cause difficulties with pump selection. A TFE pump uses heat input to the system to increase the pressure and temperature of the working fluid, rather than the work input in a standard mechanical pump. This paper compares the net power output achievable using both mechanical and TFE pumps with SORC and TFC systems. The results suggest that the TFE pump could be a viable option for TFC systems